The Effect of Disinfecting Irreversible Hydrocolloid Impressions on Bacterial Count - Salma A. Bahannan (Journal of King Abdulaziz University: Medical Sciences, 2023)
This study aims to investigate the efficacy of the different concentrations of sodium hypochlorite on the count of bacteria found in irreversible hydrocolloid impressions. Forty-six mandibular irreversible hydrocolloid impressions were collected at King Abdulaziz University. They were submersed in sterilized containers with sterile distilled water. Different concentrations of sodium hypochlorite solutions were used as a disinfectant with a submersion time of one minute. All samples investigated exhibited bacterial growth. The geometric mean of bacterial count was significantly different according to the patients’ gender. However, the difference was significant for sodium hypochlorite concentrations depending on gender and type of bacteria. The highest geometric mean of bacterial count was for male, while the lowest was for female. There was significant difference between types of bacteria with higher count of gram positive cocci. Sodium hypochlorite at 1% concentration and one minute immersion time has been shown to be an effective disinfectant to eliminate bacteria efficiently from irreversible hydrocolloid impressions.